Macroprudential Policy : An Organizing Framework. (Policy Papers; Policy Paper, 2011)
MCM conducted a survey in December 2010 to take stock of international experiences with financial stability and the evolving macroprudential policy framework. The survey was designed to seek information in three broad areas: the institutional setup for macroprudential policy, the analytical approach to systemic risk monitoring, and the macroprudential policy toolkit. The survey was sent to 63 countries and the European Central Bank (ECB), including all countries in the G-20 and those subject to mandatory Financial Sector Assessment Programs (FSAPs). The target list is designed to cover a broad range of jurisdictions in all regions, but more weight is given to economies that are systemically important (see Annex for details). The response rate is 80 percent. This note provides a summary of the survey's main findings.